Hubungan Pemahaman Isi Pesan Iklan Xl Hotrod 4G LTE Paket Truly Unlimited Dengan Minat Beli Produk Kartu XL - Bulkis, Achmad (Interaksi: Jurnal Ilmu Komunikasi, 2016)
The phenomenon of "cost war" between mobile phone operators which followed by a decrease in cost policy, would bring benefits to communications service users. This thing happens as the result of telecommunications world development that rapidly increase to inform and persuade the society.The learning hierarchy theory explains that any information (including advertising of certain products) will give exposure to the consumers and consequently changes their cognitive component including awareness, attention and understanding of consumers towards the product which can led to the further changesThis type of this research is explanatory research that explain the relationship or correlation between the level of understanding the advertising messages (X1) and buying interest on XL card product (Y). The population of this research is village residents of Pleburan, Southern District of Semarang.The results showed that higher levels of understanding advertising messages XL is is directly proportional to the higher level of buying interest on XL card, otherwise the lower level of understanding advertising messages XL is directly proportional to the lower buying interest on XL card.Keywords: The learning Hierarcy, cost wars, the internet, buying interest, understanding messages